Identification of the local stiffness reduction of a damaged composite plate using the virtual fields method - Kim, J.-H.; Pierron, F.; Wisnom, M. R.; Kashif, Syed Muhammad (Science Direct, 2007)
In the present study, a damage detection problem is formulated as the identiﬁcation of the spatial stiﬀness distribution in a damaged composite plate. Full-ﬁeld heterogeneous curvature ﬁelds obtained from an optical deﬂectometry technique are processed by using the virtual ﬁelds method adapted to retrieve the 2D stiﬀness distribution map of a damaged carbon-epoxy plate. The method not only picks up the location of the damage but also provides a fairly good estimate of the stiﬀness reduction in the damaged area. In this paper, the procedure is described, validated on simulated measurements and some initial experimental results are given. 2007 Elsevier Ltd. All rights reserved.